EP156/#955 Variability in high risk endometrial cancer risk in native versus us asians – a population analysis of US and Asia. (4th December 2022) - Wong, Deanna; Liao, Cheng-I; Kapp, Daniel; Darcy, Kathleen; Tian, Chunqiao; Chan, Chloe; Johnson, Caitlin; Cohen, Joshua; Chan, John K
Abstract : Objectives: To identify trends associated with incidence of high risk endometrial cancers in native versus US Asians. Methods: Data were obtained from the United States Cancer Statistics and Republic of China Cancer Registry from 2001–2017. We defined high risk cancers as grade 3 endometrial (G3E), serous, clear cell, and carcinosarcoma. SEER*Stat 8.3.9.2 and Joinpoint regression program 4.9.0.0 were used to calculate trends. Results: Of 55, 031 endometrial cancer patients, 28, 204 (51%) were US and 26, 827 (49%) were native Asians. In subset, serous cancer incidence (per 100, 000) in 2017 was highest in US Asians (serous 1.25, G3E 1.15, carcinosarcoma 0.82) whereas G3E was over four fold higher than other cells types in native Asians (G3E 2.63, serous 0.64, carcinosarcoma 0.51). Over the 17 year study period, the incidence of high risk cancers increased annually at 2.3% in US Asians (serous increase: 6.3%) compared to 21.9% in native Asians (G3E increase: 14.8%) (p<0.001). In analyzing mortality trends, US Asians had a higher annual increase in mortality compared to native Asians (+2.11% vs -2.99%). US Asians had an over two fold higher risk of death for ages 70+ at 22.9 (per 100, 000) compared to 10.6 in native Asians. Conclusions: The incidence for high risk uterine cancer is increasing significantly more in the Republic of China vs. US. However, mortality rates are higher in the US. Further research is needed to better understand the social determinants and regional differences that may contribute to these trends.